The Effect of Butterfly Hug on Reducing Anxiety in Pre-Operation Patients at Jatiwinangun Hospital, Purwokerto - Wardani, Intan Putri Yumanita; Sebayar, Septian Mixrova; Burhan, Asmat (Jurnal Ilmiah Wahana Pendidikan, 2024)
Anxiety in patients who are about to undergo surgery is usually related to all kinds of foreign procedures that the patient must undergo and also threats to life safety due to surgical procedures and anesthesia. One of the non-pharmacological therapies is relaxation therapy by administering a Butterfly Hug, which is an intervention to reduce anxiety levels in pre-operative patients. This study aims to determine the effect of administering the Butterfly Hug on reducing anxiety in preoperative patients. This type of research is quasi-experimental with a pretest-posttest control group design. The sample in this research was a purposive sampling of 66 respondents. Data was taken using the HARS anxiety measurement. From this study, the Wilcoxon test results were obtained with a mean difference intervention value of -10.7 (p) 0.001. And the control group with a mean difference value of -3.85 with (p) 0.001. Mann Whitney U test with a mean difference value of -6.00 (-8.93, -3.13) with (p) 0.001. The results of the study showed that there was a difference before and after administering the Butterfly Hug on preoperative patient anxiety at the Jatiwinangun Special Surgery Hospital, Purwokerto. Giving a Butterfly Hug can be a method that can be used for patients who experience anxiety before surgery.